Analysis of the Effect of Total Quality Management (TQM) on Performance in the Regional Financial Institutions in Pontianak City - bosman hutahaean (Jurnal Kewidyaiswaraan, 2021)
Abstract The limited quality of human resources owned and the lack of instruments used and the lack of support from employees in access to performance appraisals will create obstacles in the objective and optimal performance appraisal. The phenomenon that occurs in the Regional Finance Board of Pontianak City, namely the performance appraisal approach that is often used by management to see performance is still traditional. Another phenomenon that occurs is the lack of attention from management in appreciating quality employees. For this reason, it is necessary to conduct a study regarding how the effect of total quality management on the performance of the Pontianak City Financial Agency. This study aims to determine the effect of Total Quality Management (TQM) on the performance of the Regional Finance Board of Pontianak City. The research is descriptive research and associative research or causal design. Qualitative data processing was done by tabulating, while quantitatively analyzed for discussion using Multiple Linear Regression. Based on the coefficient of determination, it can be concluded that the magnitude of the influence of self-potential quality, process quality and performance quality on the ups and downs or variations in the performance of employees of the Pontianak City Regional Finance Agency is 47.10%. Simultaneously it can be concluded that the variables of self-potential quality, process quality and performance quality simultaneously have a significant effect on the respondent's performance. Partially the variables of self-potential quality and performance quality in this study have a significant effect on the respondent's performance, so that Ho is rejected and Ha is accepted. Partially the process quality variable in this study has no significant effect on the respondent's performance. Keywords: Quality, Total, Management, Performance